Triaxial Tests on Dry-wet Cycle and Creep Behavior of High-fill Coarse-grained Soil - WU Guoli; JI Binbin; LIANG Junjun; HUANG Zhongchun; XIONG Tanqing (Renmin Zhujiang)
After the Baihetan Dam reservoir area is impounded, the high fill site will experience the rise and fall of water level for a long time, which is very disadvantageous to the deformation and stability of the site. This paper focuses on the stability of high-fill sites. It is part of the Baihetan Dam project in the water-level-fluctuating zone of the resettlement area in the reservoir area. The research examines the effects of wet-dry cycles and saturation on coarse-grained soil. Methods include large-scale triaxial shear and creep tests. The investigation assesses stress-strain relationships and shear morphology. It also evaluates the long-term strength and deformation laws. Key conclusions are presented as follows: ① The strength of coarse-grained soil gradually decreases with an increase in the number of dry-wet cycles. ② When the number of dry-wet cycles n≤3, coarse-grained soil samples first shrink and then dilate; when n >3, coarse-grained soil only undergoes shear deformation. ③ The peak deviating stress of coarse-grained soil decreases gradually with the increase in the number of dry-wet cycles, and the higher the confining pressure, the greater the effect of dry-wet cycles on the damage and deterioration of the shear strength of coarse-grained soil. ④ The long-term strength of coarse-grained soil is lower than that of shear failure strength. The drop range of low confining pressure is smaller, generally reaching 80% or even higher of shear failure strength under normal circumstances; under high confining pressure, the long-term strength damage of coarse-grained soil is greater because of particle breakage.